Umbilical Cord-Derived Mesenchymal Stem Cells Inhibit Cadherin-11 Expression by Fibroblast-Like Synoviocytes in Rheumatoid Arthritis - Cheng Zhao; Lu Zhang; Wei Kong; Jun Liang; Xinyun Xu; Hongyan Wu; Xuebing Feng; Bingzhu Hua; Hong Wang; Lingyun Sun (Journal of Immunology Research)
This study aimed to determine whether umbilical cord-derived mesenchymal stem cells (UCMSC) regulate Cadherin-11 (CDH11) expression by fibroblast-like synoviocytes (FLS) in rheumatoid arthritis (RA). FLS were isolated from the synovium of RA and osteoarthritis (OA) patients. FLS from RA patients were cocultured with UCMSC in a transwell system. CDH11 mRNA levels in FLS were tested, and levels of soluble factors expressed by UCMSC, such as indoleamine 2,3-dioxygenase (IDO), hepatocyte growth factor (HGF), and interleukin- (IL-) 10, were determined. IDO, HGF, and IL-10 were upregulated in cocultures, so that appropriate inhibitors were added before determination of CDH11 expression. The effects of UCMSC on arthritis were investigated in the collagen-induced arthritis (CIA) model in Wistar rats. FLS from RA patients expressed higher CDH11 levels than those from OA patients, and this effect was suppressed by UCMSC. The inhibitory effect of UCMSC on CDH11 expression by FLS was abolished by suppression of IL-10 activity. CDH11 expression in synovial tissues was higher in the context of CIA than under basal conditions, and this effect was prevented by UCMSC administration. IL-10 mediates the inhibitory effect of UCMSC on CDH11 expression by FLS, and this mechanism might be targeted to ameliorate arthritis.